Forests Without Frugivores and Frugivores Without Forests – An Investigation Into the Causes of a Paradox in One of the Last Archipelagos Colonized by Humans - Albert, Sébastien; Flores, Olivier; Ah-Peng, Claudine; Strasberg, Dominique (Frontiers in Ecology and Evolution, 2021)
The Mascarenes are sadly famous worldwide for the massive extinction of their native vertebrates since recent human colonization. However, extinction patterns show astonishing disparities between the two main islands and between lineages of forest vertebrates. On Réunion (2512 km², 3070 m), most large-bodied vertebrates, especially frugivores, collapsed by the first half of the 18th century where about a third of native habitats remains, while several have survived longer and some still exist on Mauritius (1865 km², 828 m) where more than 95% of native habitats have been transformed. Considering lineages of forest vertebrates shared by both islands (23 genera, 53 species), we test the hypothesis that differing patterns of lowland suitable habitat destruction is the main cause behind this paradox. Before that, we assess the potential impact of other major drivers of extinctions since first contact with humans. Firstly, Mauritius shows earlier and more introductions of mammal predators known for their devastating impact (except northern islets which have thus become important sanctuaries for several squamates). Secondly, settlers were inveterate hunters on both islands, but while Réunion was overhunted before Mauritius, the burst of human population in the latter in late 18th century has not led to the rapid extinction of all large native vertebrates. These two factors alone therefore cannot explain the observed paradox. Rather, the early destruction of lowland habitats (<400 m) on Réunion is concomitant with most extinctions of forest vertebrate, notably frugivores that rapidly lost most lowland habitats dominated by large fleshy-fruited plants. Moreover, landform-induced fragmentation has likely decreased the ability of adjacent habitats to act as effective refuges. Conversely, Mauritius retained suitable low-fragmented habitats until the late 19th which probably allowed, at least for a time, several native vertebrates to escape from multiple human-induced disturbances. Despite the almost total destruction of native habitats since then on Mauritius, conservation actions have saved several threatened vertebrate species that play a fundamental role in the functioning of native ecosystems. The fact that there are now more favorable habitats on Reunion than on Mauritius argues for the rewilding of Reunion with these extant large vertebrates.